Open Unemployment Rate Based on Education Level at 2015-2018 - Tanjung, Amries Rusli; David, David; Renaldo, Nicholas; Putra, Rizaldi; Musa, Sulaiman (First Ciera Publisher, 2024)
The research aims to examine the relationship between education levels and the Open Unemployment Rate (TPT) in Indonesia from 2015 to 2018. This study employs a quantitative research approach using secondary data analysis. A descriptive and inferential statistical approach will be used to identify trends and correlations between education and unemployment. While vocational education shows promising results in reducing unemployment, general high school graduates face higher unemployment risks due to a lack of specialized skills. However, statistical analysis suggests that education alone is not the sole determinant of unemployment, and other factors such as economic conditions, skill mismatches, and technological changes must also be considered. The analysis covers only 2015-2018 data, which may not fully capture long-term employment trends or the impact of recent economic and technological shifts. Future research can expand the research period beyond 2015-2018 to analyze how unemployment trends change over time, especially in response to economic crises or technological advancements.